A novel tetra-primer ARMS-PCR approach for the molecular karyotyping of chromosomal inversion 2Ru in the main malaria vectors Anopheles gambiae and Anopheles coluzzii - Pichler, Verena; Sanou, Antoine; Love, R. Rebecca; Caputo, Beniamino; Pombi, Marco; Toe, Kobie Hyacinth; Guelbeogo, Moussa W.; Sagnon, N’Fale; Ferguson, Heather M.; Ranson, Hilary; Torre, Alessandra della; Besansky, Nora J. (Parasites & vectors, 2023)
Chromosomal inversion polymorphisms have been associated with adaptive behavioral, physiological, morphological and life history traits in the two main Afrotropical malaria vectors, Anopheles coluzzii and Anopheles gambiae. The understanding of the adaptive value of chromosomal inversion systems is constrained by the feasibility of cytological karyotyping. In recent years in silico and molecular approaches have been developed for the genotyping of most widespread inversions (2La, 2Rb and 2Rc). The 2Ru inversion, spanning roughly 8% of chromosome 2R, is commonly polymorphic in West African populations of An. coluzzii and An. gambiae and shows clear increases in frequency with increasing rainfall seasonally and geographically. The aim of this work was to overcome the constraints of currently available cytological and high-throughput molecular assays by developing a simple PCR assay for genotyping the 2Ru inversion in individual specimens of both mosquito species. We designed tetra-primer amplification refractory mutation system (ARMS)-PCR assays based on five tag single-nucleotide polymorphisms (SNPs) previously shown to be strongly correlated with 2Ru inversion orientation. The most promising assay was validated against laboratory and field samples of An. coluzzii and An. gambiae karyotyped either cytogenetically or molecularly using a genotyping-in-thousands by sequencing (GT-seq) high-throughput approach that employs targeted sequencing of multiplexed PCR amplicons. A successful assay was designed based on the tag SNP at position 2R, 31710303, which is highly predictive of the 2Ru genotype. The assay, which requires only one PCR, and no additional post-PCR processing other than electrophoresis, produced a clear banding pattern for 98.5% of the 454 specimens tested, which is a 96.7% agreement with established karyotyping methods. Sequences were obtained for nine of the An. coluzzii specimens manifesting 2Ru genotype discrepancies with GT-seq. Possible sources of these discordances are discussed. The tetra-primer ARMS-PCR assay represents an accurate, streamlined and cost-effective method for the molecular karyotyping of the 2Ru inversion in An. coluzzii and An. gambiae. Together with approaches already available for the other common polymorphic inversions, 2La, 2Rb and 2Rc, this assay will allow investigations of the adaptive value of the complex set of inversion systems observed in the two major malaria vectors in the Afrotropical region.